Preparation method and application of a lignin-based composite adsorbent

CN122974282APending Publication Date: 2026-10-27YULIN VOCATIONAL & TECH COLLEGE +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611366514.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-04
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,活性炭也存在显著的技术局限性:一方面,活性炭的孔径分布通常以微孔为主,介孔和大孔比例较低,这导致其在处理分子尺寸较大的多环芳烃、胶体物质或腐殖酸类大分子有机物时,传质阻力极大,大分子难以深入内部孔道,吸附容量受到限制;另一方面,活性炭在吸附饱和后的再生过程较为繁琐,热再生能耗高且易造成吸附剂损耗,此外在粉末活性炭的使用过程中,固液分离难度大,容易随水流流失

Benefits of technology

(1)本发明采用木质素和单宁酸构建芳香有机复合骨架,并在其内部原位形成Fe3O4,使有机吸附骨架与磁性无机相形成复合结构,在保留木质素芳香吸附特性的同时赋予材料磁响应性能,有利于吸附处理完成后的固液快速分离。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122974282A_ABST
    Figure CN122974282A_ABST
Patent Text Reader

Abstract

The present application provides a preparation method and application of a lignin-based composite adsorbent, and belongs to the field of water treatment agents. The adsorbent comprises lignin, tannic acid, Fe3O4, a surface functionalization group and quaternized chitosan. The present application constructs a multi-stage pore aromatic organic skeleton with lignin and tannic acid and anchors Fe3O4; a functional layer containing zwitterions and reversible sites is constructed on the surface through GMA / SBMA / AA copolymer; and the quaternized chitosan is in a dynamic combination state of 'partial covalent and partial ionic association'. The structure has the performances of aromatic adsorption, multi-stage pore mass transfer, dynamic flocculation and rapid magnetic separation, and significantly improves the synergistic removal efficiency and interface stability of multi-scale pollutants in complex high-salinity coal chemical wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of water treatment agents, and particularly relates to a method for preparing and applying a lignin-based composite adsorbent. Background Technology

[0002] Coal chemical industry is the process of converting coal into gaseous, liquid, and solid fuels and chemicals through chemical processing. It mainly includes technologies such as coal gasification, coal liquefaction, and coking. During coal chemical production, a large amount of wastewater is generated. This wastewater is typically characterized by complex composition, high concentrations of organic pollutants, high toxicity, and high levels of inorganic salts. It contains not only large amounts of recalcitrant organic compounds such as phenols, biphenyls, polycyclic aromatic hydrocarbons, and heterocyclic compounds, but also suspended solids, colloidal substances, and high concentrations of sulfides, cyanides, and ammonia nitrogen. If this wastewater is discharged directly without effective advanced treatment, it will pose a significant threat to the ecological environment and human health. Therefore, developing efficient, economical, and environmentally friendly advanced treatment technologies for coal chemical wastewater has always been a key research focus and challenge in the field of water treatment.

[0003] Among existing advanced technologies for treating coal chemical wastewater, adsorption is widely used due to its advantages such as simple operation, high treatment efficiency, no secondary pollution products, and strong adaptability. The core of adsorption technology lies in the performance of the adsorption material. Currently, common adsorbents used for treating coal chemical wastewater mainly include activated carbon, zeolite, resin, and some biomass-based adsorption materials.

[0004] Activated carbon is currently the most widely used adsorbent in industry. It possesses a well-developed microporous structure and a high specific surface area, exhibiting good adsorption and removal capabilities for small-molecule organic pollutants in coal chemical wastewater. However, activated carbon also has significant technical limitations: Firstly, the pore size distribution of activated carbon is typically dominated by micropores, with a low proportion of mesopores and macropores. This results in extremely high mass transfer resistance when treating large-molecule organic compounds such as polycyclic aromatic hydrocarbons, colloidal substances, or humic acids, making it difficult for large molecules to penetrate deep into the internal pores and limiting the adsorption capacity. Secondly, the regeneration process of activated carbon after adsorption saturation is cumbersome, with high energy consumption for thermal regeneration and a tendency to cause adsorbent loss. Furthermore, in the use of powdered activated carbon, solid-liquid separation is difficult, and it is easily lost with water flow.

[0005] Synthetic resins and zeolite molecular sieves are also commonly used adsorption materials. Synthetic resins have good chemical stability and specific selectivity, but their production cost is relatively high, and their synergistic adsorption capacity for mixed pollutants in complex water is insufficient; although zeolite molecular sieves have a regular pore structure, their surface is highly hydrophilic, resulting in low adsorption affinity for highly hydrophobic aromatic organic compounds in coal chemical wastewater.

[0006] In recent years, the preparation of biomass-based adsorbents using natural polymer resources (such as lignin and chitosan) has attracted widespread attention. Lignin, as the main structural framework of vascular plants, is rich in various active functional groups such as phenolic hydroxyl groups, alcoholic hydroxyl groups, and carboxyl groups, and possesses an aromatic network structure, theoretically exhibiting good affinity for pollutants with aromatic rings in coal chemical wastewater. However, unmodified natural lignin suffers from drawbacks such as low specific surface area, high water solubility (especially under alkaline conditions), poor mechanical strength, and a simple pore structure, resulting in low adsorption capacity and easy dissolution and loss in aqueous phase when used directly as an adsorbent.

[0007] To address the shortcomings of biomass materials, existing modification methods primarily employ cross-linking, grafting, or composite material preparation to improve their performance. For example, physical or chemical cross-linking is used to construct polymer networks to enhance water stability, or specific functional groups are introduced to strengthen the binding force on pollutants. However, current technologies still face numerous bottlenecks when treating complex coal chemical wastewater characterized by high salinity and high ionic strength. Poor adaptability to complex water quality: High concentrations of inorganic salt ions in coal chemical wastewater can cause electrostatic shielding of charged functional groups on the surface of the adsorbent, significantly reducing the electrostatic force between the adsorbent and pollutants, resulting in a significant decrease in adsorption performance. Low multi-scale pollutant synergistic removal rate: Pollutants in wastewater include small molecule organic matter, large molecule recalcitrant substances and suspended colloids. Adsorption materials with single pore size or single action mechanism are difficult to simultaneously take into account the effective mass transfer and retention of pollutants of different sizes and properties. Solid-liquid separation and recovery are difficult: Many high-performance powder adsorbents are well dispersed in the aqueous phase, but after adsorption, they are extremely difficult to recover efficiently through traditional sedimentation or filtration methods, which limits their potential for continuous industrial application.

[0008] Therefore, overcoming the problems of existing adsorption materials having a simple pore structure, being prone to failure in high-salt and complex water quality, and being difficult to efficiently separate and recover after adsorption, and developing an adsorption material with good mass transfer channels, strong interfacial stability and easy separation is a technical problem that urgently needs to be solved in the field of deep treatment of coal chemical wastewater. Summary of the Invention

[0009] The first objective of this invention is to provide a lignin-based composite adsorbent, comprising the following components by weight: Lignin, 40.0-60.0 parts; Tannic acid, 8.0-20.0 parts; Ferrous salts and ferric salts, totaling 12.0-30.0 parts; Surface functionalized components, 5.0-12.0 parts; Quaternized chitosan, 2.0-8.0 parts; In this process, the lignin and tannic acid form an aromatic organic composite framework, and the ferrous salt and ferric salt form Fe3O4 in situ under alkaline conditions. The Fe3O4 is dispersed and anchored within the aromatic organic composite framework, thereby enabling the lignin-based composite adsorbent to form an organic-inorganic composite structure. The aromatic organic composite framework has a hierarchical porous structure composed of micropores and mesopores, wherein the micropore diameter is <2nm and the mesopore diameter is 2-50nm. The surface functionalization component is a copolymer functionalized layer formed by glycidyl methacrylate, sulfobetaine methacrylate, and acrylic acid, and is covalently linked to the hydroxyl groups in the aromatic organic composite skeleton through some of the epoxy groups in the glycidyl methacrylate; the functionalized layer contains unreacted epoxy groups, sulfobetaine structures, and carboxyl groups; the quaternized chitosan is distributed on the surface of the functionalized layer and in the pore region of the hierarchical porous structure, and some of the quaternized chitosan is covalently linked to the unreacted epoxy groups in the functionalized layer, and some of the quaternized chitosan is reversibly linked to the functionalized layer.

[0010] Preferably, in the surface functionalized component, the molar ratio of glycidyl methacrylate, sulfobetaine methacrylate and acrylic acid is 15-25:55-70:10-20.

[0011] Preferably, the Fe3O4 has a particle size of 10-50 nm; the lignin-based composite adsorbent has a specific surface area of ​​250-600 m². 2 / g, total pore volume is 0.30-0.90cm³ 3 / g.

[0012] Preferably, the lignin has a weight-average molecular weight of 1000-5000 Da, a phenolic hydroxyl content of 1.5-3.5 mmol / g, and a carboxyl content of 0.3-1.2 mmol / g.

[0013] Preferably, in the quaternized chitosan, the mass ratio of covalently linked quaternized chitosan to reversibly linked quaternized chitosan is 1:1 to 1:4.

[0014] The covalently linked quaternized chitosan forms C-N covalent bonds with the residual epoxy groups in the surface functionalized component through amino groups; the reversibly linked quaternized chitosan forms ion associations with the carboxyl groups or carboxylates in the surface functionalized component through quaternary ammonium groups.

[0015] Preferably, the mesopore volume accounts for 50-80% of the total pore volume of the lignin-based composite adsorbent.

[0016] Preferably, the saturation magnetization of the lignin-based composite adsorbent is 20-50 emu / g.

[0017] A second objective of this invention is to provide a method for preparing the aforementioned lignin-based composite adsorbent, comprising the following steps: S1. Preparation of magnetic hierarchical porous framework: Lignin, tannic acid, pore-forming agent, ferrous salt and ferric salt are added to a solvent and mixed. The system is adjusted to alkalinity so that lignin and tannic acid form an aromatic organic composite framework, and ferrous ions and ferric ions form Fe3O4 in situ. After mild heat treatment to decompose sodium bicarbonate gas and create pores, polyethylene glycol is removed by solvent elution to obtain a magnetic lignin-based framework with microporous and mesoporous hierarchical porous structure. S2. Surface Functionalization and Quaternized Chitosan Loading: The magnetic lignin-based framework is added to a reaction system containing glycidyl methacrylate, sulfobetaine methacrylate, and acrylic acid. A redox initiation system composed of ammonium persulfate and sodium bisulfite is added, and the system is adjusted to weak alkalinity to copolymerize glycidyl methacrylate, sulfobetaine methacrylate, and acrylic acid. Simultaneously, some epoxy groups in glycidyl methacrylate undergo ring-opening grafting with hydroxyl groups on the surface of the magnetic lignin-based framework to form a surface functionalized layer. After the functionalized layer is formed and some unreacted epoxy groups remain on the surface, quaternized chitosan is added. Some of the quaternized chitosan forms a covalent bond with the residual epoxy groups in the functionalized layer, while the other part of the quaternized chitosan forms a reversible bond with the functionalized layer to obtain the lignin-based composite adsorbent. The pore-forming agent includes sodium bicarbonate and polyethylene glycol.

[0018] The third objective of this invention is to provide the application of the aforementioned lignin-based composite adsorbent in the adsorption of coal chemical wastewater.

[0019] This invention's lignin-based composite adsorbent achieves the synergistic removal of organic and colloidal pollutants from coal chemical wastewater through a multi-level structure of "magnetic hierarchical porous framework—surface functionalized layer—dynamic quaternized chitosan layer". First, the aromatic structures in lignin and tannic acid together form an aromatic organic composite framework, utilizing the polar groups such as hydroxyl, phenolic hydroxyl, and carboxyl groups contained in both to form an organic framework with high surface activity. Fe3O4 is formed in situ and dispersed within this framework, creating a composite structure between the organic framework and the inorganic magnetic phase. Fe3O4 not only acts as a magnetic node but also enhances the overall density and magnetic response of the composite material, enabling the composite adsorbent, after adsorbing pollutants, to rapidly separate from the treatment system under an applied magnetic field.

[0020] During the framework formation process, a hierarchical pore structure composed of micropores and mesopores is constructed using a pore-forming agent. Micropores provide a high number of surface adsorption sites, while mesopores serve as mass transfer channels for pollutants to enter the particle interior, allowing organic pollutants in coal chemical wastewater to gradually enter the internal channels from the outside of the particle. The high proportion of mesopore volume to total pore volume reduces the mass transfer resistance encountered by large organic molecules entering the channels, and together with the high specific surface area and total pore volume, improves the utilization rate of the effective adsorption interface. Therefore, the aromatic structure formed by lignin and tannic acid, the hierarchical pore structure, and the surface polar groups together constitute the basic adsorption system of the composite adsorbent. The aromatic structure can bind to aromatic organic pollutants in coal chemical wastewater through π-π interactions and hydrophobic interactions, while polar groups such as hydroxyl, carboxyl, and phenolic hydroxyl groups can further enhance the binding of pollutants on the adsorbent surface through hydrogen bonds and dipole interactions.

[0021] A copolymer functionalized layer composed of glycidyl methacrylate, sulfobetaine methacrylate, and acrylic acid was further constructed on the surface of a magnetic hierarchical porous framework. Some epoxy groups in the glycidyl methacrylate segments underwent ring-opening reactions with the hydroxyl groups in the lignin and tannic acid frameworks, covalently fixing the copolymer functionalized layer to the framework surface and preventing significant desorption due to physical adsorption alone. Simultaneously, some unreacted epoxy groups were retained during copolymerization, allowing them to continue serving as covalent linkage sites for subsequent quaternization of chitosan. Thus, a continuous interfacial structure of "framework covalent fixation – HACC secondary linkage" was formed within the same functionalized layer.

[0022] The sulfobetaine structure introduced by sulfobetaine methacrylate has opposite charge centers, enabling it to form a stable hydration layer in the aqueous phase. This reduces the direct shielding effect of inorganic salt ions on the functional groups on the material surface under high ionic strength conditions and improves the interfacial stability of the adsorbent in complex coal chemical wastewater. The carboxyl or carboxylate groups in the acrylic acid segments form ion associations with the quaternary ammonium groups in quaternized chitosan, providing reversible binding sites for the quaternized chitosan. Therefore, SBMA and AA do not simply add hydrophilic groups, but rather form zwitterionic and reversibly binding structures respectively within the same copolymer functional layer, giving the surface functional layer a structural basis that combines a stable interface and dynamic bonding.

[0023] Quaternized chitosan is further distributed on the surface of the functionalized layer and in the hierarchical porous region, forming two different binding states. One portion of the quaternized chitosan undergoes a ring-opening reaction with the residual epoxy groups in the functionalized layer to form C-N covalent bonds, thus being stably fixed to the surface of the composite adsorbent. The other portion of the quaternized chitosan mainly forms reversible ionic associations with the carboxyl groups or carboxylates in the functionalized layer through quaternary ammonium groups, and is retained within the functionalized layer and porous region due to the spatial confinement of the hierarchical pores and the entanglement of polymer chain segments. This results in a quaternized chitosan layer with both stable and dynamically bound portions.

[0024] In the treatment of coal chemical wastewater, the cationic groups in quaternized chitosan can interact electrostatically with negatively charged colloidal particles, humic substances, and some macromolecular organic pollutants, and promote pollutant aggregation through the bridging effect of polymer chain segments. Compared with HACC layers that are entirely covalently fixed, the reversible connection part can undergo a certain degree of dissociation and recombination when the pollutant concentration, interfacial ionic environment, and adsorbent surface binding state change, thus making the flocculation active sites dynamically available; while the covalently fixed part maintains the basic structure of the HACC layer, reducing the overall loss of HACC in high-salinity systems. Therefore, by combining the two binding states, a dynamic flocculation interface is formed while maintaining the structural stability of the material.

[0025] In summary, this invention provides a basic adsorption interface through a lignin / tannic acid aromatic framework, improves pollutant mass transfer and effective adsorption site utilization through a microporous-mesoporous hierarchical pore structure, imparts magnetic response to the composite material through Fe3O4, constructs a stable zwitterionic and reversible binding interface through a GMA / SBMA / AA copolymer functionalized layer, and forms a dynamic flocculation layer through partially covalently and partially reversibly connected quaternized chitosan, thereby forming a composite pollutant removal mechanism that combines adsorption, flocculation, and magnetic separation.

[0026] II. Beneficial Effects Compared with existing lignin adsorbent materials, the present invention has the following beneficial effects: (1) The present invention uses lignin and tannic acid to construct an aromatic organic composite framework and forms Fe3O4 in situ inside it, so that the organic adsorption framework and the magnetic inorganic phase form a composite structure. While retaining the aromatic adsorption characteristics of lignin, it also imparts magnetic response properties to the material, which is beneficial to the rapid solid-liquid separation after the adsorption treatment is completed.

[0027] (2) The present invention constructs a multi-level pore structure composed of micropores and mesopores by using a pore-forming agent, and improves the mass transfer process of pollutants inside the adsorbent by designing a pore structure with a high proportion of mesopore volume; combined with a high specific surface area and total pore volume, it can improve the utilization rate of the adsorption interface, and is especially suitable for the synergistic removal of organic pollutants of different molecular sizes in coal chemical wastewater.

[0028] (3) In this invention, a functionalized layer of GMA / SBMA / AA copolymer is constructed on the surface of a magnetic hierarchical porous framework. The functionalized layer is stably fixed on the surface of the adsorption framework by forming a covalent connection between the epoxy group of GMA and the hydroxyl group of the framework. At the same time, sulfobetaine structure and carboxyl structure are introduced to give the surface a stable zwitterionic structure and reversible binding sites, thereby improving the interfacial stability of the material in complex, high-salt wastewater environments.

[0029] (4) In this invention, quaternized chitosan is set into two states: covalent connection and reversible connection. The covalent connection part can improve the fixation stability of the HACC layer, while the reversible connection part can provide dynamic flocculation sites. This avoids the excessive fixation of flocculation sites caused by a single covalent fixation method, and also avoids the loss of a large amount of HACC due to a simple physical loading method, thus taking into account both material stability and dynamic flocculation ability.

[0030] (5) The present invention adopts the preparation sequence of “first forming a magnetic hierarchical porous framework, then constructing a GMA / SBMA / AA functionalized layer, and finally introducing quaternized chitosan”, so that after the GMA functionalized layer is formed, some epoxy groups are still retained for HACC connection, thereby reducing the possibility of GMA and HACC competing reaction before the functionalized layer is formed, which is beneficial to obtaining the predetermined surface composite structure.

[0031] (6) The present invention utilizes the synergistic effects of multiple mechanisms, including aromatic structure adsorption, hierarchical pore structure mass transfer, surface functional group binding, quaternized chitosan flocculation, and Fe3O4 magnetic separation, to enable the obtained lignin-based composite adsorbent to simultaneously achieve pollutant removal, adaptability to complex water quality, and solid-liquid separation performance after treatment. It is suitable for the adsorption treatment of coal chemical wastewater. Attached Figure Description

[0032] Appendix Figure 1 Transmission electron microscope (TEM) images of the magnetic hierarchical porous frameworks prepared in Examples 1, 2, 3, and 4 of this invention.

[0033] Appendix Figure 2 The image shows the magnetization curves (VSM) of the magnetic hierarchical porous frameworks prepared in Examples 1, 2, 3, and 4 of this invention.

[0034] Appendix Figure 3 Fourier transform infrared (FT-IR) spectra of the adsorbents prepared in Examples 1 and 12 of this invention.

[0035] Appendix Figure 4 The nitrogen adsorption-desorption isotherms of the adsorbents prepared in Examples 1, 9, and 10 of this invention are shown.

[0036] Appendix Figure 5 The images show the pore size distribution of the adsorbents prepared in Examples 1, 9, and 10 of this invention. Detailed Implementation

[0037] To better understand the present invention, the present invention will be further described below with reference to specific serial numbers. The terminology used in the serial numbers is for describing specific embodiments and does not constitute a limitation on the scope of protection of the present invention.

[0038] In the specific implementation methods, unless otherwise specified, the experimental methods used are all conventional methods, and the materials and reagents used are all commercially available unless otherwise specified.

[0039] Unless otherwise specified, percentages, % and so on in the specific implementation method are assumed to be mass percentages.

[0040] Some of the raw materials used in this invention are as follows: I. Lignin The lignin A used in this invention has a weight-average molecular weight of 2850 Da, a phenolic hydroxyl content of 2.42 mmol / g, and a carboxyl content of 0.68 mmol / g.

[0041] The lignin B used in this invention has a weight-average molecular weight of 4380 Da, a phenolic hydroxyl content of 3.18 mmol / g, and a carboxyl content of 1.05 mmol / g.

[0042] The lignin C used in this invention has a weight-average molecular weight of 6850 Da, a phenolic hydroxyl content of 1.18 mmol / g, and a carboxyl content of 1.46 mmol / g. II. Fe3O4 Formation Raw Materials The ferrous salt used in this invention is ferrous chloride tetrahydrate (FeCl2·4H2O).

[0043] The iron salt used in this invention is ferric chloride hexahydrate (FeCl3·6H2O).

[0044] It should be noted that the Fe3O4 in this invention is formed in situ using ferrous and ferric salts, rather than by pre-adding commercially available Fe3O4.

[0045] III. Pore-forming agent The sodium bicarbonate used in this invention has a purity of 99.5% and an average particle size of 18.5 μm.

[0046] The polyethylene glycol (PEG) used in this invention is PEG-4000, with a number-average molecular weight of 4000 Da and a hydroxyl value of 25.8 mgKOH / g.

[0047] IV. Glycidyl methacrylate The glycidyl methacrylate (GMA) used in this invention has a molecular weight of 142.15 Da.

[0048] V. Sulfobetaine methacrylate The sulfobetaine methacrylate (SBMA) used in this invention has a molecular weight of 279.37 Da.

[0049] VI. Acrylic acid The acrylic acid (AA) used in this invention has a molecular weight of 72.06 Da.

[0050] VII. Quaternized Chitosan The quaternized chitosan used in this invention has a degree of deacetylation of 89.4%, a degree of quaternization substitution of 32.6%, and a weight-average molecular weight of 1.85 × 10⁻⁶. 5 Da; A 1 wt% quaternized chitosan solution was prepared with 1 wt% acetic acid solution at 25℃, and its dynamic viscosity was 214 mPa·s.

[0051] VIII. Free Radical Redox Initiation System The present invention uses ammonium persulfate (APS) and sodium bisulfite (NaHSO3).

[0052] 9. pH adjusters This invention uses sodium hydroxide.

[0053] 10. Elution Solvent The elution solvents used in this invention are deionized water and anhydrous ethanol, wherein the conductivity of deionized water is not higher than 1 μS / cm and the purity of anhydrous ethanol is not lower than 99.5%.

[0054] Example 1: Preparation of a magnetic hierarchical porous framework (M-1) I. Preparation of Magnetic Hierarchical Porous Framework 1. Preparation of reactants Lignin A: 40.0g Tannic acid: 8.0g Ferrous chloride tetrahydrate: 3.23g Ferric chloride hexahydrate: 8.79g Pore-forming agent: Sodium bicarbonate: 6.0g PEG-4000: 4.0g Dispersion solvent: 400 mL deionized water, 100 mL anhydrous ethanol 2. Specific preparation steps Organic precursor dispersion and iron ion coordination enrichment: In a 1000 mL three-necked flask equipped with an electric stirrer, thermometer, and nitrogen protection device, 300 mL of deionized water and 100 mL of anhydrous ethanol were added. Then, 40.0 g of lignin A, 8.0 g of tannic acid, 6.0 g of sodium bicarbonate, and 4.0 g of PEG-4000 were added sequentially according to the above dosage. The mixture was thoroughly dispersed at 35 °C and 300 rpm for 45 min to form a uniform brown-black organic framework precursor dispersion.

[0055] In-situ crosslinking and Fe3O4 in-situ mineralization: 3.23 g of ferrous chloride tetrahydrate and 8.79 g of ferric chloride hexahydrate were dissolved in 100 mL of deionized water and added dropwise to the above three-necked flask. Stirring was continued for 30 min to allow the iron ions to fully complex with the phenolic hydroxyl and carboxyl groups on the surface of lignin and tannic acid. Subsequently, the pH of the system was slowly adjusted to 10.5 using a 2.0 mol / L sodium hydroxide solution.

[0056] Mild foaming and solvent extraction elution: The system was heated to 75°C and reacted under mild humid heat conditions for 2.5 h. During this process, sodium bicarbonate decomposed upon heating, releasing CO2 microbubbles, which induced the formation of micropores and defect structures within the not-yet-fully-solidified organic network, while simultaneously promoting microphase separation of PEG-4000. After the reaction was complete, the solid-liquid mixture was cooled to room temperature, and the solid product was collected by vacuum filtration.

[0057] Elution and drying: The filter cake was redispersed in 500 mL of anhydrous ethanol / deionized water (1:1 volume ratio) mixed solvent and washed and extracted three times at 50 °C to thoroughly remove unreacted residues, generated soluble inorganic salts, and the soft template agent PEG-4000. The solid was then washed with pure deionized water until the conductivity of the filtrate was less than 5 μS / cm. The washed solid was dried in a vacuum drying oven at 60 °C for 12 h to obtain a magnetic lignin-based framework with a microporous and mesoporous hierarchical structure.

[0058] 3. Physical property test results of magnetic hierarchical porous framework The structure and properties of the obtained magnetic lignin-based framework (M-1) were characterized, and the physical properties are as follows: Saturation magnetization (VSM): 35.2 eμ / g (enables rapid solid-liquid separation within 30s under an applied magnetic field); Specific surface area (BET method): 322.5 m² 2 / g; Total pore volume (BJH method): 0.41 cm³ 3 / g; Mesoporous pore volume percentage: 55.8% (mesoporous pore volume is 0.229 cm³) 3 / g, mesopore size distribution is concentrated in 8.5-22.0nm, and micropore size is less than 1.8nm). Fe3O4 nanoparticle size (TEM): 18.5-35.0 nm (uniformly dispersed within the lignin-tannin aromatic framework and at pore wall nodes, with no macroscopic aggregation observed).

[0059] Example 2: Preparation of a magnetic hierarchical porous framework (M-2) 1. Preparation of reactants Lignin A: 50.0g Tannic acid: 14.0g Ferrous chloride tetrahydrate: 5.85g Ferric chloride hexahydrate: 15.10g Pore-forming agent: Sodium bicarbonate: 10.0g PEG-4000: 12.0g Dispersion solvent: 500 mL deionized water, 150 mL anhydrous ethanol 2. Specific preparation steps Organic precursor dispersion and iron ion coordination enrichment: In a 1000 mL three-necked flask equipped with an electric stirrer, thermometer, and nitrogen protection device, 400 mL of deionized water and 150 mL of anhydrous ethanol were added. Then, 50.0 g of lignin A, 14.0 g of tannic acid, 10.0 g of sodium bicarbonate, and 12.0 g of PEG-4000 were added sequentially according to the above amounts. The mixture was thoroughly dispersed at 40 °C and 350 rpm for 60 min to form a uniform brown-black organic framework precursor dispersion.

[0060] In-situ crosslinking and Fe3O4 in-situ mineralization: 5.85 g of ferrous chloride tetrahydrate and 15.10 g of ferric chloride hexahydrate were dissolved in 100 mL of deionized water and added dropwise to the above three-necked flask. Stirring was continued for 40 min to allow the iron ions to fully complex with the phenolic hydroxyl and carboxyl groups on the surface of lignin and tannic acid. Subsequently, the pH of the system was slowly adjusted to 11.0 using a 2.5 mol / L sodium hydroxide solution.

[0061] Mild foaming and pore formation followed by solvent extraction and elution: The system was heated to 80°C and reacted under mild humid heat conditions for 3.0 h. During this process, sodium bicarbonate decomposed upon heating, releasing a large amount of CO2 microbubbles, which induced the formation of micropores and defect structures within the organic network. Simultaneously, a relatively high amount of PEG-4000 formed continuous micelle phase separation zones under thermal phase transition, directionally constructing a large proportion of mesoporous channels. After the reaction was completed, the solid-liquid mixture was cooled to room temperature, and the solid product was collected by vacuum filtration.

[0062] Elution and drying: The filter cake was redispersed in 600 mL of anhydrous ethanol / deionized water (1:1 volume ratio) and washed and extracted four times at 55 °C to thoroughly remove unreacted residues, soluble inorganic salts, and the soft template agent PEG-4000. The filtrate was then washed with pure deionized water until the conductivity was less than 5 μS / cm. The washed solid was dried in a vacuum drying oven at 65 °C for 14 h to obtain the magnetic hierarchical porous framework (M-2).

[0063] 3. Physical property test results of the magnetic hierarchical porous framework (M-2) The structure and properties of the obtained magnetic lignin-based framework (M-2) were characterized, and the physical properties are as follows: Saturation magnetization (VSM): 50.4 eμ / g (extremely strong magnetic responsiveness, complete solid-liquid separation can be achieved within 15s under an external magnetic field); Specific surface area (BET method): 548.2 m² 2 / g Total pore volume (BJH method): 0.79 cm³ 3 / g; Mesoporous pore volume percentage: 70.3% (mesoporous pore volume is 0.555 cm³) 3 / g, mesopore size is concentrated in the range of 12.0-35.0 nm, and micropore size is less than 1.7 nm). Fe3O4 nanoparticles (TEM size): 20.0-42.0 nm (high density and uniform anchoring within the lignin-tannin aromatic framework and mesoporous pore walls, with good crystallinity).

[0064] Example 3: Preparation of a magnetic hierarchical porous framework (M-3) 1. Preparation of reactants Lignin B: 60.0g Tannic acid: 20.0g Ferrous chloride tetrahydrate: 8.02g Ferric chloride hexahydrate: 21.98g Sodium bicarbonate: 15.0g PEG-4000: 18.0g Dispersion solvent: 600 mL deionized water, 200 mL anhydrous ethanol 2. Specific preparation steps Organic precursor dispersion and iron ion coordination enrichment: In a 2000 mL three-necked flask equipped with an electric stirrer, thermometer, and nitrogen protection device, 500 mL of deionized water and 200 mL of anhydrous ethanol were added. Then, 60.0 g of lignin B, 20.0 g of tannic acid, 15.0 g of sodium bicarbonate, and 18.0 g of PEG-4000 were added sequentially according to the above dosage. The mixture was thoroughly dispersed at 45 °C and 400 rpm for 60 min to form a high-viscosity, uniform, brownish-black organic framework precursor dispersion.

[0065] In-situ crosslinking and Fe3O4 in-situ mineralization: 8.02 g of ferrous chloride tetrahydrate and 21.98 g of ferric chloride hexahydrate were dissolved in 100 mL of deionized water and added dropwise to the above three-necked flask. Stirring was continued for 45 min. The high phenolic hydroxyl content of lignin B promotes high-density coordination crosslinking of iron ions. Subsequently, the pH of the system was slowly adjusted to 11.5 using a 3.0 mol / L sodium hydroxide solution.

[0066] High-efficiency foaming and pore-forming combined with solvent extraction and elution: The system was heated to 85°C and the reaction was maintained at this temperature for 3.5 hours. During this process, the high concentration of sodium bicarbonate underwent violent decomposition, releasing a large amount of CO. 2 The gas induces the formation of an ultra-high density microporous network; simultaneously, a large amount of PEG-4000 causes intense microphase separation, constructing interconnected ultra-high proportion mesoporous channels within the cross-linked network. After the reaction, the solid-liquid mixture is allowed to cool naturally to room temperature, and the solid product is collected by vacuum filtration.

[0067] Elution and drying: The filter cake was dispersed in 800 mL of anhydrous ethanol / deionized water (1:1 volume ratio) mixed solvent and hot-extracted and washed four times at 60 °C to thoroughly remove residual soft template PEG-4000 and soluble salts. It was then washed with deionized water until the conductivity of the filtrate was less than 5 μS / cm. The washed solid was dried in a vacuum drying oven at 70 °C for 16 h to obtain the magnetic hierarchical porous framework (M-3).

[0068] 3. Physical property test results of the magnetic hierarchical porous framework (M-3) The structure and properties of the obtained magnetic lignin-based framework (M-3) were characterized, and the physical properties are as follows: Saturation magnetization (VSM): 58.9 eμ / g (extremely rapid magnetic response, capable of efficient solid-liquid separation within 10s under an applied magnetic field); Specific surface area (BET method): 698.5 m² 2 / g; Total pore volume (BJH method): 1.14 cm³ 3 / g; Mesopore volume percentage: 79.8% (mesopore volume is 0.91 cm3 / g, mesopore size is concentrated in 15.0-45.0 nm, micropore size is less than 1.6 nm); Fe3O4 nanoparticle size (TEM): 25.0-48.0 nm (uniformly distributed in the framework and mesoporous walls, without macroscopic phase separation).

[0069] Example 4: Preparation of a magnetic hierarchical porous framework (M-4) 1. Preparation of reactants Lignin C: 40.0g Tannic acid: 8.0g Ferrous chloride tetrahydrate: 3.23g Ferric chloride hexahydrate: 8.79g Sodium bicarbonate: 6.0g PEG-4000: 4.0g Dispersion solvent: 300 mL deionized water, 100 mL anhydrous ethanol 2. Specific preparation steps Organic precursor dispersion and iron ion coordination enrichment: In a 1000 mL three-necked flask equipped with an electric stirrer, thermometer, and nitrogen protection device, add 300 mL of deionized water and 100 mL of anhydrous ethanol. Then, add 40.0 g of lignin C, 8.0 g of tannic acid, 6.0 g of sodium bicarbonate, and 4.0 g of PEG-4000 sequentially according to the above amounts. Disperse thoroughly for 60 min at 35 °C and 300 rpm (due to the large molecular weight of lignin C, the dissolution time should be appropriately extended) to form a brownish-black dispersion.

[0070] In-situ crosslinking and Fe3O4 in-situ mineralization: 3.23 g of ferrous chloride tetrahydrate and 8.79 g of ferric chloride hexahydrate were dissolved in 100 mL of deionized water and added dropwise to the three-necked flask. Stirring continued for 45 min. Due to the significant decrease in the phenolic hydroxyl content of lignin C, the number of coordination crosslinking sites with iron ions decreased, resulting in a looser network crosslinking density. Subsequently, the pH of the system was slowly adjusted to 10.5 using a 2.0 mol / L sodium hydroxide solution, allowing lignin and tannic acid to crosslink under alkaline conditions, while simultaneously promoting the in-situ co-precipitation of iron ions to form nano-Fe3O4.

[0071] Mild foaming and pore formation followed by solvent extraction and elution: The system was heated to 75°C and maintained at this temperature for 2.5 h. Sodium bicarbonate decomposed upon heating, releasing CO2 gas and inducing the formation of a porous structure; PEG-4000 underwent microphase separation. After the reaction was complete, the solid-liquid mixture was cooled to room temperature, and the solid product was collected by vacuum filtration.

[0072] Elution and drying: The filter cake was redispersed in 500 mL of anhydrous ethanol / deionized water (1:1 v / v) mixture and washed and extracted three times at 50 °C to thoroughly remove unreacted residues and PEG-4000. The solid was then washed with pure deionized water until the conductivity of the filtrate was less than 5 μS / cm. The washed solid was dried in a vacuum oven at 60 °C for 12 h to obtain the comparative magnetic hierarchical porous framework (M-4).

[0073] 3. Physical property test results of the magnetic hierarchical porous framework (M-4) Saturation magnetization (VSM): 31.5 eμ / g (some Fe3O4 slightly agglomerates due to insufficient surface coordination sites, resulting in a slight decrease in magnetic response); Specific surface area (BET method): 215.8 m² 2 / g (Loose cross-linking leads to insufficient micropore development, resulting in a significant decrease in specific surface area); Total pore volume (BJH method): 0.27 cm³ 3 / g; Mesoporous pore volume percentage: 45.2% (mesoporous pore volume is 0.122 cm³) 3 / g, high molecular weight leads to increased phase separation size and increased pore collapse rate); Fe3O4 nanoparticle size (TEM): 15.0-55.0 nm (the particle size distribution is widened, and some particles grow in size due to insufficient spatial confinement).

[0074] Transmission electron microscopy (TEM) images of the magnetic hierarchical porous frameworks prepared in Examples 1, 2, 3, and 4 are shown below. Figure 1 As shown; the magnetization curve (VSM) is as follows. Figure 2 As shown.

[0075] Application Example 1: Preparation of Lignin-based Composite Adsorbent (C-1) 1. Preparation of reactants Magnetic hierarchical porous framework: 60.0 g of the magnetic hierarchical porous framework (M-1) prepared in Example 1. Surface-functionalized monomer components (total mass 5.0 g, GMA:SBMA:AA molar ratio = 15:70:10): Glycidyl methacrylate (GMA): 0.48g (3.38mmol) Sulfobetaine methacrylate (SBMA): 4.37 g (15.64 mmol) Acrylic acid (AA): 0.15g (2.08mmol) Quaternized chitosan (HACC): 2.0g Redox initiation system: Ammonium persulfate (APS) 0.05g, sodium bisulfite (NaHSO3) 0.025g Reaction medium and washing solvent: 300 mL deionized water, 150 mL anhydrous ethanol 2. Specific preparation steps Framework pre-dispersion and monomer adsorption: In a 500 mL four-necked flask equipped with an electric stirrer, reflux condenser, thermometer, and nitrogen protection device, 200 mL of deionized water and 50 mL of anhydrous ethanol were added. 60.0 g of the M-1 framework powder prepared in Example 1 was added and ultrasonically dispersed for 30 min. Subsequently, 0.48 g of GMA, 4.37 g of SBMA, and 0.15 g of AA were added sequentially, and the mixture was pre-equilibrated for 45 min under stirring at 30 °C and 250 rpm to allow the ternary functional monomers to fully diffuse and adsorb onto the hierarchical channels and outer surface of M-1.

[0076] In-situ initiated copolymerization and surface epoxy ring-opening grafting: The pH of the system was adjusted to 8.0 (weakly alkaline environment) by titration with 1.0 mol / L NaOH solution. A redox initiator consisting of 0.05 g APS and 0.025 g NaHSO3 was added, and the temperature was raised to 55 °C for 2.0 h. During this stage, the acrylate double bonds underwent free radical copolymerization to form functionalized polymer segments; simultaneously, under weakly alkaline heating conditions, approximately 40% of the epoxy groups in the GMA segments underwent nucleophilic ring-opening reactions with the phenolic / alcoholic hydroxyl groups on the surface of the M-1 backbone, achieving covalent grafting and fixation of the functionalized copolymer layer on the surface of the M-1 backbone, while retaining unreacted residual epoxy groups in the system.

[0077] Dual-state loading (covalent + reversible ionic association) of quaternized chitosan: 2.0 g of quaternized chitosan (HACC) was pre-dissolved in 50 mL of deionized water and added dropwise to the above reaction system. The temperature was raised to 65 °C and the reaction was continued for 3.0 h.

[0078] Post-treatment and drying: After the reaction, the product was cooled to room temperature. Magnetic solid-liquid separation was performed under an external magnetic field, and the supernatant was discarded. The product was washed three times each with deionized water and anhydrous ethanol to remove ungrafted free homopolymer and residual initiator until the washing solution was neutral and the conductivity was less than 5 muS / cm. The precipitate was vacuum dried at 60℃ for 12 h, and then ground to obtain the lignin-based composite adsorbent (C-1).

[0079] 3. Physical property test results of lignin-based composite adsorbent (C-1) The physical structure and magnetic properties of the obtained product C-1 were characterized: Saturation magnetization (VSM): 20.3 emu / g (due to the non-magnetic polymer functional layer and HACC layer loaded on the surface, the magnetic properties are lower than those of the M-1 framework, but still maintain good magnetic responsiveness, and can achieve efficient capture and separation of external magnetic field within 40s). Specific surface area (BET method): 282.4 m² 2 / g (Polymer segment modification and pore filling lead to a moderate reduction in specific surface area); Total pore volume (BJH method): 0.32 cm³ 3 / g; Mesoporous pore volume percentage: 55.1% (mesoporous pore volume is 0.176 cm³) 3 / g, the main mesoporous channels are preserved, resulting in low mass transfer resistance); The ratio of quaternized chitosan bound states (determined by chemical analysis) is: the mass ratio of HACCs forming covalent bonds to those forming reversible ion-associated bonds is 1:3.8.

[0080] Application Example 2: Preparation of Lignin-based Composite Adsorbent (C-2) 1. Preparation of reactants Magnetic hierarchical porous framework: 70.0 g of the magnetic hierarchical porous framework (M-2) prepared in Example 2. Surface-functionalized monomer components (total mass 8.5g, GMA:SBMA:AA molar ratio = 20:62:15): GMA: 0.95g (6.68mmol) SBMA: 7.19g (25.74mmol) AA: 0.36g (5.00mmol) Quaternized chitosan (HACC): 5.0g Initiation system: APS 0.08g, NaHSO3 0.04g 2. Preparation steps and test results Following the steps of Application Example 1, replace the M-1 skeleton with the M-2 skeleton and add the corresponding mass of monomer and HACC.

[0081] Saturation magnetization (VSM): 38.6 emu / g; Specific surface area (BET method): 425.6 m² 2 / g; Total pore volume (BJH method): 0.61 cm³ 3 / g; Mesoporous pore volume percentage: 68.5%; HACC covalent / reversible linkage quality ratio: 1:2.5.

[0082] Application Example 3: Preparation of Lignin-based Composite Adsorbent (C-3) 1. Preparation of reactants Magnetic hierarchical porous framework: 80.0g of the magnetic hierarchical porous framework (M-3) prepared in Example 3. Surface-functionalized monomer components (total mass 10.0 g, GMA:SBMA:AA molar ratio = 22:60:18): GMA: 1.23g (8.65mmol) SBMA: 8.26g (29.57mmol) AA: 0.51g (7.08mmol) Quaternized chitosan (HACC): 7.0g Initiation system: APS 0.10g, NaHSO3 0.05g 2. Preparation steps and test results Follow the steps in Application Example 1, using the M-3 skeleton.

[0083] Saturation magnetization (VSM): 42.1 emu / g; Specific surface area (BET method): 510.2 m² 2 / g; Total pore volume (BJH method): 0.82 cm³ / g; Mesoporous pore volume percentage: 77.8%; HACC covalent / reversible linkage quality ratio: 1:1.8.

[0084] Application Example 4: Preparation of Lignin-based Composite Adsorbent (C-4) 1. Preparation of reactants Magnetic hierarchical porous framework: 60.0g of magnetic hierarchical porous framework (M-4) prepared in Example 4. Surface functionalized monomer components and HACC: Same as in Application Example 1.

[0085] 2. Preparation steps and test results The procedure was followed as in Application Example 1, using the M-4 framework. Due to the low density of phenolic hydroxyl groups on the M-4 surface, the GMA grafting rate decreased.

[0086] Saturation magnetization (VSM): 18.2 emu / g; Specific surface area (BET method): 165.4 m² 2 / g; Total pore volume (BJH method): 0.21 cm³ 3 / g; Mesoporous pore volume percentage: 42.3%; HACC covalent / reversible linkage quality ratio: 1:4.5.

[0087] Application Example 5: Preparation of Lignin-based Composite Adsorbent (C-5) 1. Preparation of reactants Magnetic hierarchical porous framework: 80.0g of the M-3 framework prepared in Example 3. Surface-functionalized monomer components (total mass 12.0 g, GMA:SBMA:AA molar ratio = 25:55:20): GMA: 1.92g (13.51mmol) SBMA: 8.30g (29.71mmol) AA: 0.78g (10.82mmol) Quaternized chitosan (HACC): 8.0g Initiation system: APS 0.12g, NaHSO3 0.06g 2. Preparation steps and test results Following the steps in Application Example 1, both the functional layer and the HACC loading amount reached their maximum limits.

[0088] Saturation magnetization (VSM): 36.2 emu / g; Specific surface area (BET method): 385.0 m² 2 / g; Total pore volume (BJH method): 0.65 cm³ 3 / g; Mesoporous pore volume percentage: 74.2%; HACC covalent / reversible linkage quality ratio: 1:1.5.

[0089] Application Example 6: Preparation of Lignin-based Composite Adsorbent (C-6) 1. Preparation of reactants Magnetic hierarchical porous framework: 80.0g of the M-3 framework prepared in Example 3. Surface functionalized monomer components: Total mass 6.0g (GMA:SBMA:AA molar ratio 18:67:15) Quaternized chitosan (HACC): 3.0g 2. Preparation steps and test results Follow the steps in Application Example 1.

[0090] Saturation magnetization (VSM): 48.2 emu / g; Specific surface area (BET method): 495.0 m² 2 / g; Total pore volume (BJH method): 0.78 cm³ 3 / g; Mesoporous pore volume percentage: 79.5%; HACC covalent / reversible linkage quality ratio: 1:2.2.

[0091] Application Example 7: Preparation of Lignin-based Composite Adsorbent (C-7) 1. Preparation of reactants (high pore volume control) Magnetic hierarchical porous framework: 80.0g of the M-3 framework prepared in Example 3 (with its foaming process adjusted to achieve a total pore volume of 1.20 cm³ / g). Surface functionalized monomer components and HACC: Same as in Application Example 3.

[0092] 2. Preparation steps and test results Follow the steps in Application Example 1.

[0093] Saturation magnetization (VSM): 39.5 emu / g; Specific surface area (BET method): 560.0 m² 2 / g; Total pore volume (BJH method): 0.90 cm³ 3 / g; Mesoporous pore volume percentage: 76.0%; HACC covalent / reversible linkage quality ratio: 1:2.0.

[0094] Application Example 8: Preparation of Lignin-based Composite Adsorbent (C-8) 1. Preparation of reactants Magnetic hierarchical porous framework: 70.0g of the M-2 framework prepared in Example 2. Surface functionalized monomer components (GMA ratio increased to 24 mol%): GMA 1.25 g, SBMA 6.20 g, AA 0.30 g Quaternized chitosan (HACC): 4.0g 2. Preparation steps and test results The steps were carried out according to Application Example 1; and the GMA ratio was increased and the ring-opening reaction time was extended (the S2 step was extended to 5.0 h) to promote the formation of more primary amines and residual epoxy groups into C-N covalent bonds.

[0095] Saturation magnetization (VSM): 37.0 emu / g; Specific surface area (BET method): 390.0 m² 2 / g; Total pore volume (BJH method): 0.55 cm³ 3 / g; Mesoporous pore volume percentage: 66.0%; HACC covalent / reversible linkage quality ratio: 1:1.15.

[0096] Application Example 9: Preparation of a single pore-forming agent (C-9) 1. Preparation of reactants Magnetic hierarchical porous framework M-5: Refer to Example 1, except that only 10.0g of sodium bicarbonate is used as the pore-forming agent, and PEG-4000 is omitted.

[0097] Surface functionalization and HACC load: Same as application example 1.

[0098] 2. Preparation steps and test results Due to the lack of microphase separation guidance from PEG-4000, it is difficult to form continuous mesoporous channels inside the material.

[0099] Saturation magnetization (VSM): 22.5 emu / g; Specific surface area (BET method): 210.0 m² 2 / g; Total pore volume (BJH method): 0.22 cm³ 3 / g; Mesopore volume percentage: 28.0% (the proportion of mesopores has decreased significantly, with micropores being the main component).

[0100] Application Example 10: Preparation of the pore-forming agent-free skeleton (C-10) 1. Preparation of reactants Magnetic hierarchical porous framework M-6: Refer to Example 1, except that no pore-forming agent is used at all (neither NaHCO3 nor PEG-4000).

[0101] Surface functionalization and HACC load: Same as application example 1.

[0102] 2. Preparation steps and test results The skeleton is severely compacted, with poor development of both micropores and mesopores.

[0103] Saturation magnetization (VSM): 24.0 emu / g; Specific surface area (BET method): 85.0 m² 2 / g; Total pore volume (BJH method): 0.09 cm³ 3 / g; Mesoporous pore volume percentage: 15.0%.

[0104] Application Example 11: Preparation of Non-functionalized Layer with Directly Loaded HACC (C-11) 1. Preparation of reactants Magnetic hierarchical porous framework: 60.0g of the M-1 framework prepared in Example 1. Quaternized chitosan (HACC): 2.0g (GMA / SBMA / AA ternary copolymer functionalization layer removed) 2. Preparation steps and test results The M-1 framework was directly mixed with HACC and then centrifuged and dried. Due to the lack of epoxy and carboxyl groups provided by the functional layer, HACC was bound only by weak physical adsorption.

[0105] Saturation magnetization (VSM): 23.0 emu / g; Specific surface area (BET method): 310.0 m² 2 / g; Loss rate test: After stirring in the aqueous phase for 24 hours, the HACC loss rate reached 68.5%.

[0106] Application Example 12: Preparation of the Zwitterionic Layer (C-12) of SBMA without modification 1. Preparation of reactants Magnetic hierarchical porous framework: 60.0g of the M-1 framework prepared in Example 1. Functional monomer components (SBMA is omitted, and GMA and AA are distributed in their original molar ratios, totaling 5.0g): GMA 3.0g, AA 2.0g Quaternized chitosan (HACC): 2.0g 2. Preparation steps and test results The lack of an zwitterionic antifouling layer of SBMA leads to a sharp decline in the material's anti-shielding ability in high-salt environments.

[0107] Saturation magnetization (VSM): 21.0 emu / g; Specific surface area (BET method): 275.0 m² 2 / g.

[0108] Application Example 13: Preparation of HACC Fully Covalently Linked (C-13) 1. Preparation of reactants Magnetic hierarchical porous framework: 60.0g of the M-1 framework prepared in Example 1. Functional monomer component: The proportion of GMA has been significantly increased to 80 mol% (without AA segments providing ion association sites). Quaternized chitosan (HACC): 2.0g 2. Preparation steps and test results Adding a ring-opening catalyst promotes the complete reaction of the primary amine group and the residual epoxy group in HACC.

[0109] HACC binding morphology: 100% covalent linkage (reversible linkage without ion association); Application Example 14: Preparation of HACC Fully Reversible Connection (C-14) 1. Preparation of reactants Magnetic hierarchical porous framework: 60.0g of the M-1 framework prepared in Example 1. Functional monomer components: GMA is eliminated, and only AA and SBMA copolymerization is used (to provide high-density -COOH). Quaternized chitosan (HACC): 2.0g 2. Preparation steps and test results HACC binding morphology: 100% ion-associated reversible linkage (no C-N covalent bonds). Application Example 15: Preparation of Components Mixed and Feeded at One Time (C-15) 1. Preparation of reactants The material ratio is exactly the same as in Application Example 1, but the reaction is not carried out in steps.

[0110] 2. Preparation steps and test results The M-1 skeleton, GMA, SBMA, AA, HACC and initiator were added to the reaction flask at the same time and the temperature was raised to react.

[0111] Results analysis: The amino groups on the HACC preferentially add to the unpolymerized GMA monomers, disrupting the free radical copolymerization process and generating a large amount of useless precipitates in the liquid phase. The grafting rate on the skeleton surface is extremely low, and the performance is severely degraded.

[0112] Application Example 16: Preparation of Commercial Pre-fabricated Fe3O4 Physical Composite (C-16) 1. Preparation of reactants Lignin A: 40.0g Tannic acid: 8.0g Commercial Fe3O4 powder (average particle size 30nm): 3.76g (without Fe) 2+ / Fe 3+ In-situ coprecipitation) The dosages of the remaining pore-forming agents, functional monomers, and HACC are the same as in Application Example 1.

[0113] 2. Preparation steps and test results Commercial Fe3O4 was forcibly physically suspended in a lignin / tannic acid system for cross-linking.

[0114] Lacking ion coordination and in-situ mineralization anchoring, Fe3O4 particles severely aggregate and detach from the organic framework, resulting in a significant decrease in saturation magnetization (VSM of only 11.2 emu / g) and a high iron loss rate during acid and alkali washing.

[0115] The Fourier transform infrared (FT-IR) spectra of the adsorbents prepared in Examples 1 and 12 are as follows: Figure 3 As shown; the nitrogen adsorption-desorption isotherms of the adsorbents prepared in Examples 1, 9, and 10 are as follows. Figure 4 As shown; the pore size distribution diagrams of the adsorbents prepared in Examples 1, 9, and 10 are as follows. Figure 5 As shown.

[0116] Test Example 1 I. Experimental Testing Methods (1) Water quality configuration and basic adsorption conditions Water quality: The water is treated by the second stage of coal gasification. The actual water quality indicators are: COD_Cr=1050mg / L, total phenols=210mg / L, turbidity=120NTU, TDS=22000mg / L (salt content), pH=8.0.

[0117] Adsorption conditions: Take 100 mL of wastewater, add 1.0 g / L of composite adsorbent, and shake and adsorb for 120 min at 25℃ and 200 rpm.

[0118] (2) Multi-scale synergistic removal of pollutants experiment Test method: After adsorption, an external magnetic field is applied to separate the supernatant. COD is then determined according to the dichromate method (HJ828-2017). Cr The total phenol concentration was determined by the 4-aminoantipyrine spectrophotometric method (HJ503-2009); the turbidity of the supernatant was measured by a portable turbidimeter, and the corresponding removal rate (%) was calculated.

[0119] (3) High salt / high ion strength shielding test Test method: NaCl was added to the above wastewater to adjust the TDS to 50000 mg / L (high-salt environment). The COD removal rate under high salt conditions was measured under the same adsorption conditions, and its retention rate (%) relative to the COD removal rate of the base wastewater was calculated (high-salt removal rate / base removal rate × 100%).

[0120] (4) Dynamic flocculation and HACC anti-loss test Test method: The adsorbent was continuously swished and stirred at high speed (500 rpm) in a 30000 mg / L NaCl solution for 48 h. The concentration of HACC released from the aqueous phase was detected by total organic carbon (TOC) analyzer and liquid chromatography, and the HACC loss rate (%) was calculated. Subsequently, the washed adsorbent was reintroduced into the new wastewater and the adsorption-magnetic separation operation was repeated. After 5 cycles, the COD removal rate and retention rate (%) of the 5th cycle were calculated.

[0121] (5) Magnetic separation kinetics and iron stability experiment Test method: After adsorption, a 0.3T permanent magnet was attached to one side of the beaker, and the magnetic separation time (s) required for the supernatant to become clear and for the adsorbent to completely separate into solid and liquid was recorded with a stopwatch; at the same time, the total dissolved iron concentration (mg / L) in the supernatant after separation was determined using an inductively coupled plasma optical emission spectrometer (ICP-OES).

[0122] The results are shown in Tables 1, 2, and 3.

[0123] Table 1

[0124] Table 2

[0125] Table 3

[0126] As shown in Tables 1, 2, and 3, the performance differences of the composite adsorbents directly stem from the degree of synergistic effect of the three components: the framework, the amphoteric functional layer, and the dual-state flocculation layer. Changes in each component have the following impacts on the physicochemical behavior and test indicators of the materials: When pore-forming agents are lacking or of a single type, materials struggle to form continuous mesoporous mass transfer channels and achieve high specific surface areas. This results in large organic molecules being unable to penetrate deep into internal adsorption sites due to steric hindrance, and polymer chains failing to achieve effective spatial confinement and entanglement, significantly reducing the removal efficiency of large molecular COD and colloidal pollutants. If in-situ co-precipitation of iron salts is eliminated and physical composite with prefabricated magnets is used, the inorganic magnetic phase, lacking site anchoring and spatial confinement by polar groups in the organic framework, is highly prone to aggregation and detachment, leading to a significant increase in magnetic separation time and dissolved iron concentration.

[0127] When the surface functionalization layer is removed or the zwitterionic monomer SBMA is lacking, the material cannot form a stable hydration layer in the aqueous phase. The ion shielding effect under high salinity weakens the binding of surface groups to contaminants, leading to a significant drop in COD removal retention rate under high salinity conditions. Furthermore, without the epoxy covalent anchoring sites provided by GMA, the functional layer and HACC rely solely on physical adsorption, resulting in severe detachment under high salinity and high-speed scouring, leading to increased HACC 48-hour loss rate and deteriorated recycling performance.

[0128] When the HACC binding state deviates from the bi-state equilibrium: if all are covalently linked, the polymer chain segments lose conformational flexibility and dynamic dissociation ability due to over-solidification, weakening the bridging flocculation effect and leading to a decrease in turbidity removal rate; if all are reversibly linked by ion association, the high-salt environment easily induces association breakage, resulting in a large amount of HACC being lost during flushing. If the stepwise reaction sequence is changed to a single-stage feeding, the competitive side reactions between components disrupt the continuous interface structure and bi-state binding morphology of the functional layer, thereby causing an overall decline in adsorption and flocculation performance.

[0129] The above detailed description is a specific description of one of the feasible embodiments of the present invention. This embodiment is not intended to limit the patent scope of the present invention. All equivalent implementations or modifications that do not depart from the present invention should be included within the scope of the technical solution of the present invention.

Claims

1. A lignin-based composite adsorbent, characterized in that, Calculated by parts by mass, it includes the following components: Lignin, 40.0-60.0 parts; Tannic acid, 8.0-20.0 parts; Ferrous salts and ferric salts, totaling 12.0-30.0 parts; Surface functionalized components, 5.0-12.0 parts; Quaternized chitosan, 2.0-8.0 parts; In this process, the lignin and tannic acid form an aromatic organic composite framework, and the ferrous salt and ferric salt form Fe3O4 in situ under alkaline conditions; the Fe3O4 is dispersed and anchored inside the aromatic organic composite framework, so that the lignin-based composite adsorbent forms an organic-inorganic composite structure. The aromatic organic composite framework has a hierarchical porous structure composed of micropores and mesopores, wherein the micropore diameter is <2nm and the mesopore diameter is 2-50nm. The surface functionalization component is a copolymer functionalized layer formed by glycidyl methacrylate, sulfobetaine methacrylate, and acrylic acid, and is covalently linked to the hydroxyl groups in the aromatic organic composite skeleton through some of the epoxy groups in the glycidyl methacrylate; the functionalized layer contains unreacted epoxy groups, sulfobetaine structures, and carboxyl groups; the quaternized chitosan is distributed on the surface of the functionalized layer and in the pore region of the hierarchical porous structure, and some of the quaternized chitosan is covalently linked to the unreacted epoxy groups in the functionalized layer, and some of the quaternized chitosan is reversibly linked to the functionalized layer.

2. The lignin-based composite adsorbent according to claim 1, characterized in that, In the surface functionalized components, the molar ratio of glycidyl methacrylate, sulfobetaine methacrylate, and acrylic acid is 15-25:55-70:10-20.

3. The lignin-based composite adsorbent according to claim 1, characterized in that, The Fe3O4 has a particle size of 10-50 nm; the lignin-based composite adsorbent has a specific surface area of ​​250-600 m². 2 / g, total pore volume is 0.30-0.90cm³ 3 / g.

4. The lignin-based composite adsorbent according to claim 1, characterized in that, The lignin has a weight-average molecular weight of 1000-5000 Da, a phenolic hydroxyl content of 1.5-3.5 mmol / g, and a carboxyl content of 0.3-1.2 mmol / g.

5. The lignin-based composite adsorbent according to claim 1, characterized in that, In the quaternized chitosan, the mass ratio of covalently linked quaternized chitosan to reversibly linked quaternized chitosan is 1:1 to 1:

4.

6. The lignin-based composite adsorbent according to claim 5, characterized in that, The covalently linked quaternized chitosan forms C-N covalent bonds with the residual epoxy groups in the surface functionalized component through amino groups; the reversibly linked quaternized chitosan forms ion associations with the carboxyl groups or carboxylates in the surface functionalized component through quaternary ammonium groups.

7. The lignin-based composite adsorbent according to claim 1, characterized in that, The mesopores account for 50-80% of the total pore volume of the lignin-based composite adsorbent.

8. The lignin-based composite adsorbent according to claim 1, characterized in that, The saturation magnetization of the lignin-based composite adsorbent is 20-50 emu / g.

9. The method for preparing the lignin-based composite adsorbent according to any one of claims 1-8, characterized in that, Includes the following steps: S1. Preparation of magnetic hierarchical porous framework: Lignin, tannic acid, pore-forming agent, ferrous salt and ferric salt are added to a solvent and mixed. The system is adjusted to alkalinity so that lignin and tannic acid form an aromatic organic composite framework, and ferrous ions and ferric ions form Fe3O4 in situ. After mild heat treatment to decompose sodium bicarbonate into gas to create pores, polyethylene glycol is removed by solvent elution to obtain a magnetic lignin-based framework with microporous and mesoporous hierarchical porous structure. S2. Surface Functionalization and Quaternized Chitosan Loading: The magnetic lignin-based framework is added to a reaction system containing glycidyl methacrylate, sulfobetaine methacrylate, and acrylic acid. A redox initiation system composed of ammonium persulfate and sodium bisulfite is added, and the system is adjusted to weak alkalinity to copolymerize glycidyl methacrylate, sulfobetaine methacrylate, and acrylic acid. Simultaneously, some epoxy groups in glycidyl methacrylate undergo ring-opening grafting with hydroxyl groups on the surface of the magnetic lignin-based framework to form a surface functionalized layer. After the functionalized layer is formed and some unreacted epoxy groups remain on the surface, quaternized chitosan is added. Some of the quaternized chitosan forms a covalent bond with the residual epoxy groups in the functionalized layer, while the other part of the quaternized chitosan forms a reversible bond with the functionalized layer to obtain the lignin-based composite adsorbent. The pore-forming agent includes sodium bicarbonate and polyethylene glycol.

10. The application of the lignin-based composite adsorbent according to any one of claims 1-8 in the adsorption of coal chemical wastewater.